Vietnam : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
Vietnam is in the process of reforming its economy, adopting market economy mechanisms, and integrating into the world economy. Like a number of countries in the process of transition to a market economy, Vietnam faces challenges in improving its laws and regulations, strengthening its institutions, and buiding capacity to improve financial accountability. While it is difficult to attain quickly all the requirements of a market economy, it is possible to focus initially on a critical subset of these requirements and take a series of steps that are compatible with the Vietnamese environment. Such a gradual approach, currently being taken by the government, should lead to tangible achievements in financial accountability over time. Experience has shown that stand-alone measures to strengthen financial accountability are not effective. These need to be complemented by parallel measures that form part of a comprehensive reform adddressing issues such as human resources, compensation structure, performance measures, and legal reform. The government should adopt a multi-pronged strategy that encompasses reforming public administration, strengthening the oversight capacity of the legislature, introducing an integrated financial management system, and building capacity and strengthening institutions responsible for ensuring accountability. In the public sector, technological changes should follow the process of administrative reform and the streamlining of processes and procedures